Use of complementary and alternative medicine in management of chemotherapy related side effects among cancer patients / Sharifah Nadia Syed Mohammad Salleh - Syed Mohammad Salleh, Sharifah Nadia (2017)
Introduction: Cancer management reduces cancer patient’s quality of life. Managing the side effects of cancer treatment is also challenging. Local data on complementary and alternative medicine (CAM) used for management of chemotherapy related side effects (CRSE) is lacking, hence leaving the cancer patients taking CAM at high risk of adverse drugs reactions due to drug- CAM interactions. Objective: The primary goal for this study is to determine the choice of CAM used as CRSE management in cancer patients and its prevalence. In addition, patient’s disclosure to their prescribers and monthly expenditure for CAM purchase were also observed. Method: This study was questionnaire based, interviewer assisted cross sectional analysis. Data were collected from cancer patients attending three departments; surgical, medical and gynecology. Results: 273 patients were recruited. 166 were CAM users for CRSE management. Prevalence of CAM use for CRSE among patients was 60.8%. High percentage of CAM users include female patients (86.7%), educated (39.8%), employed (79.1%) and married (74.1%). Breast cancer patients are the highest users of CAM for CRSE (97.4%). The three highest type of CAM used for CRSE were nutritional supplements (n=166) herbal preparations (n=154) and traditional Malay therapy (n=147). 51% (n=85) patients were introduced to CAM treatment by family members or close friends, however started using CAM after listening to testimonials by other cancer survivors. 82.5% (n=137%) patients admitted to their prescribers on their CAM use. 21.1% (n=29) doctors agree or encourage use of CAM, 65% (n=89) disagree to CAM and suggest to discontinue CAM treatments or use while 13.9% (n=19) are unbiased. Conclusion: The prevalence of CAM use in management of CRSE is increasing. The high use of CAM for CRSE management is associated to gender, employment, marriage status and education level. Three common choice of CAM used for CRSE relief are dietary supplements, herbal medicine and traditional Malay therapy. Advertisement and support groups play a significant role in giving influence on cancer patients’ treatment decisions. There are still prescribers who disagree with combining chemotherapy with complementary medicine, which inhibit the patients to share their use of CAM, hence making patients to use the treatments or products discretely without fully knowing or understanding the danger that might occur due to drug-CAM interactions.